1997
DOI: 10.1136/bmj.315.7111.810
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia after acute stroke

Abstract: GD, Dyker AG, Lees KR. Is hyperglycaemia an independent predictor of poor outcome after acute stroke? Results of a long term follow up study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…[120] A neuroendocrine stress response[121] and an inflammatory response[122] may also play a role in generating hyperglycemia.…”
Section: Glucosementioning
confidence: 99%
“…[120] A neuroendocrine stress response[121] and an inflammatory response[122] may also play a role in generating hyperglycemia.…”
Section: Glucosementioning
confidence: 99%
“…The possible pathogenesis of hyperglycemia in acute ischemic stroke is stress response or pre-existing impaired glucose intolerance in patients without history of diabetes 9 , 10 , although there is no sufficient evidence regarding the management of hyperglycemia in these patients. Furthermore, the studies regarding hyperglycemia in lacunar stroke have reported inconclusive findings, and one meta-analysis of 1375 patients with ischemic stroke from two placebo-controlled trials reported that hyperglycemia did not harm patients with lacunar stroke, and that moderate hyperglycemia (> 8mmol/L) might even be beneficial 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Acute hyperglycemia also increased the risk of a poor functional recovery in non-diabetic stroke survivors with a relative risk of 1.4. Other studies have not found hyperglycemia to be an independent predictor of stroke outcome and have suggested that hyperglycemia simply reflects a catecholamine-based stress response to a more severe stroke [62,63,64]. …”
Section: Control Of Glycemiamentioning
confidence: 99%